3785 Shares Topic: Rewrite my paper free
July 19, 2019 / By Francisca
Question: I have to rewrite quadratic equations in expanded form into factored form. The thing is, I have a few problems that have a (-1x^2) instead of (1x^2). I'm a bit confused... Can anyone help and provide an explanation? e.g. -1x^2-10x-24=0  Darcey | 7 days ago
👍 202 | 👎 7

We found more questions related to the topic: Rewrite my paper free Originally Answered: How do you solve a quadratic equation with just three points?
Equation of a quadratic equation is: y = ax^2 +bx +c you have 3 points A(x1, y1) B(x2, y2) C(x3, y3) substitute the 3 points into the equation y1 = ax1^2 +bx1 +c y2 = ax2^2 +bx2 +c y3 = ax3^2 +bx3 +c you have 3 equations with 3 unknowns to solve for a, b and c Brande
Well, first, to get rid of your problem you can multiply the whole equation by -1 to get x^2+10x+24=0. Then, to factor, you think about what two multiples of the third term add up to the coefficient (the number before the variable) of the second term. This always works when the coefficient of the first number is 1, but if it isn't, it will not. 6 times 4 = 24 and 6+4=10. Therefore, the factored form of this equation is (x+6)(x+4)=0 or (x+4)(x+6)=0, either way is the same.
👍 80 | 👎 -2 Alea
First the quadratic formulation for a given equation ax^2+bx+c=0 is right here: -b±sqrt(b^2+(-4*a*c)) / 2a as a effect enable: a=4 b=6 c-4 utilising your calculator, you will desire to get the two values for x (the effect from the quadratic equation above) to be 0.5 and -2 There you flow!
👍 74 | 👎 -11

If you have your own answer to the question rewrite my paper free, then you can write your own version, using the form below for an extended answer.